The Effects of β-Glucan on Pig Growth and Immunity - Vetvicka, Vaclav; Vannucci, Luca; Sima, Petr (The open biochemistry journal, 2014)
With increasing amounts of data showing significant immunostimulating effects of glucan, it is not surprising that attention is also focused on commercially farmed animals. Despite marked progress, development of more efficient uses of glucan in pig farming still needs substantial additional research.
Keywords: Immunity; Health; Glucan; Immunostimulation; Pig.; Nutrition